The Future of Virology is Synthetic - Richard Allen White (mSystems, 2021)
ABSTRACT The virosphere (i.e., global virome) represents a vast library of unknown genes on the planet. Synthetic biology through engineering principles could be the key to unlocking this massive global gene repository. Synthetic viruses may also be used as tools to understand “the rules of life” in diverse microbial ecosystems. Such insights may be crucial for understanding the assembly, diversity, structure, and scale of virus-mediated function. Viruses directly affect resilience, stability, and microbial community selection via death resistance cycles. Interpreting and clarifying these effects is essential for predicting the system’s ecology, evolution, and ecosystem stability in an increasingly unstable global climate. A “silent looming pandemic” due to multidrug-resistant microbes will directly impact the global economy, and synthetic virology could provide a future strategy of treatment using targeted viral therapy. This commentary will discuss current techniques for manipulating viruses synthetically, contributing to improved human health and sustainable agriculture.